Peran Pondok Pesantren Kebudayaan dalam Menjawab Fenomena Krisis Identitas Budaya - Ade Zuki Damanik; Abil Aslama Awalia; Nisrina Nadzifah; Rahmah Juniarti; Dahlia Ma’rufi Anshori (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In the era of globalization, identity and cultural crises are increasingly prevalent in many societies, including in Indonesia. This is caused by the integration of new cultures and values that obscure the roots of local traditions. Cultural Islamic boarding schools play an important role in responding to this phenomenon by offering a holistic approach that combines religious education with the preservation of local culture. The Ndalem Wongsorogo Cultural Islamic Boarding School in Kendal, Central Java, is a real example in the effort to preserve local traditions and identities. This boarding school not only teaches religious values, but also arts, culture, and practical skills such as barista and fine arts. This approach allows students to develop a more holistic understanding of their identity, combining faith with local wisdom. With routine activities such as gamelan practice, klenengan, and hadroh, this boarding school functions as a center for the preservation of arts and traditions as well as a repository of cultural heritage. This article explores the role of cultural boarding schools in maintaining cultural identity amidst the flow of globalization and offers insights into how this institution can become an adaptive educational model that answers the challenges of modernization without abandoning cultural roots